3251 Psoas muscle caliber as a predictor of negative outcomes in elderly trauma patients. (27th March 2019) - Meader, Anna; Carter, Damien; Clark, David; Stefan, Mihaela
Abstract : OBJECTIVES/SPECIFIC AIMS: Aim 1: To evaluate whether psoas muscle size on CT imaging can be used as univariate predictor for increased risk of morbidity and mortality in trauma patients 65 years or older with rib fractures. Primary outcomes will be 30 day mortality. Secondary outcomes will include length of stay, 30 day readmission rate, need for operative/procedural intervention, ICU days, ventilator days, discharge to rehabilitation. Aim 2: An eventual goal of the project will be to use the results of the single variable psoas size study to inform the development of a predictive model for readmission rate in this population based on clinical variables present at admission. METHODS/STUDY POPULATION: This retrospective cohort study will utilize the Maine Trauma Registry to conduct a database review for all persons 65 years of age and older admitted to Maine Medical Center between January 1, 2015 and December 31, 2017 with rib fracture as diagnosed by CT imaging. Psoas caliber will be measured on admission CT. Patient outcomes will be assessed via EMR review. RESULTS/ANTICIPATED RESULTS: Anticipate finding a relationship between decreased psoas caliber and increase in 30 day mortality and post trauma complications. DISCUSSION/SIGNIFICANCE OF IMPACT: If a relationship is demonstrated between decreased psoas caliber and poor outcomes in elderly patients with rib fractures, this early indicator could be used to identify those patients at most risk, for whom targeted interventions may make the greatest difference. Knowing a measure of frailty could also help guide goals of care discussions, because it would allow clinicians to have a more detailed understanding of a patient's baseline. Those patients identified as frail could be admitted to an ICU level of care and more closely monitored and treated. Alternatively, some frail patients and their families may choose to focus more on comfort and quality of life after achieving a better understanding of a patient's frailty and risk, changing the direction of care provided. Being able to identify the higher risk patients with an objective measure would allow clinicians to provide more personalized medicine.